COMPASSIONATE USE OF INVESTIGATIONAL DRUG DURING EMERGENCY CONDITIONS AND ASSOCIATED ETHICAL ASPECTS, CHALLENGES, AND BENEFITS - ASHIQUE, SUMEL; KHATUN, TAHAMINA (Asian Journal of Pharmaceutical and Clinical Research, 2021)
“Compassionate Use,” also known as expanded access, is a method by which patients with a life-threatening or seriously debilitating disease that has no satisfactory treatment alternatives can gain access to new drugs outside the context of a clinical trial. Compassionate use (CU) of unlicensed drugs serves the need of patients with the serious debilitating disease in the absence of alternative approved therapies. CU does allow limited access to new products currently in clinical trials. However, it must be remembered that there are strict guidelines to follow. As with any new drug-device or treatment, there are strict guidelines determined by the Food and Drug Administration and study sponsor, especially for CU. This article contains the use of an investigational drug in emergencies, which are the ethical aspects for getting approval, the major challenges in taking a compassionate drug, and the benefits for dying patients.